Hidroesterificação do óleo de crambe empregando catálise enzimática - Tavares, Fernanda (2014)
Due to climatic conditions and shortage of petroleum-based fuels, the search for new sources aimed to solve such problems is notorious. Biodiesel is a fuel which has been extensively studied over the years, but there are still many problems involving the production processes and also the raw materials used. Thus, the present work aims to study a process that has presented interesting features in terms of energy and cost, even though it has still been understudied, and in addition, seeks to employ the crambe oil, an oil that is not used in the food chain and has considerable advantages in the biofuel production. The hydroesterification is a process which involves two steps, first being a hydrolysis process and the second an oil esterification of the hydrolyzed oil. In this work a central composite rotational design (DCCR) 2³ was employed to study the following variables: temperature, water/oil molar ratio content and yield of catalyst in the content of fatty acids through the enzymatic hydrolysis of crambe oil. The enzyme used in this study was the commercial lipase Lypozyme RM IM. The planning results showed that the optimum conditions were achieved in the studied limits and thus additional experiments were made necessary to reach the conclusion that the ideal reaction temperature is 60°C. The molar ratio between water and oil was not significant for the planning, which is probably due to the fact that the conditions studied were of excess water, to ensure that the reaction occurred until the end. The content of the catalyst was the most significant factor and to optimize the use of catalyst in the reaction a new 2² design was conducted to evaluate the effects of rotation level and catalyst content. Rotation level was the most significant effect, demonstrating thereby that the external mass transfer is an important factor in the enzymatic hydrolysis reaction of crambe oil. Experimental data of the kinetic study of the enzymatic hydrolysis of crambe oil was obtained under conditions of 2.2 mass percentage of total substrate, water/oil molar ratio of 10:1, level of rotation of 790 rpm at temperatures of 50°C, 55°C and 60°C. A mathematical model found in available literature was used to describe the data. The enzymatic hydrolysis reaction reached a good conversion into free fatty acids, reaching 77%. The esterification reaction was carried out using free fatty acids obtained from the hydrolysis optimum condition, under 5% mass percentage of Amberlyst 15® catalyst, methanol/oil molar ratio of 30:1, at temperatures of 65 °C and 80 °C during 4 hours of reaction, and the best result obtained was a 49% of conversion of methyl esters. Although the end result of the work did not achieved a high conversion into esters, the results established trends to be used in future works as it was observed that the process of hydroesterification is promising since it enables the use of unrefined raw materials and mild conditions, resulting in lower production costs for biodiesel.